ANALISIS DAYA DUKUNG LAHAN DI KOTA BAUBAU, SULAWESI TENGGARA - Muhammad Mu’min Fahimuddin; Baba Barus; Sri Mulatsih (Diponegoro University, 2016)
Carrying capacity in a broad sense can be defined as the ability of environment to support activities to a specific level. This study aimed to describe the carrying capacity of land in Baubau City. The methods used are land physical approach and land economic approach. The land physical approach has conducted by suitability analysis of land capability on the actual land use and spatial pattern plan. The land economic approach has been done by calculating the economic value generated by each class of land use. The results showed that of the total area of 29,313.96 ha Baubau City, physically carrying capacity of land is relatively good, where 21,890.80 ha (74.68 %) is suitable and 7,423.13 ha (25.32 %) is not suitable, whereas economically with the assumption to feasible lives is Rp8,750,000 per year, meet the carrying capacity 442,083 of life or 3.1 times of total population of Baubau City. This study recommended that land management in Baubau city should be directed to control the constructed land and the protection of agricultural land and forestry.